Theoretical Studies: The Use of Art therapy in Counseling for Children - Tobing, Christine Masada H; Oktasari, Maria; Stevani, Hayu (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Children have the beautiful moment if they grow according to their stage and having the supporting environment due to their self-potential. But in this stage is not always running well, so it cause a problem for children which is needed to be solved, that is by giving them the counseling service. This given counseling services to children need special technique because of the different character between children and adult. Technique used in this article is the Art Therapy. It used to solve children problem in its relation with private symbols, social, love and caring, discipline, law and religion. In other words, the using of art therapy in counseling is needed by children in reaching the optimal development and the solving problem to children.